High-pressure eclogite facies metamorphism and decompression melting recorded in paleoproterozoic accretionary wedge adjacent to probable ophiolite from Itaguara (southern São Francisco Craton - Brazil). (October 2019) - de Oliveira Chaves, Alexandre; Alexandre Goulart, Luiz Emanoel; Coelho, Raphael Martins; Miranda, Daniel Andrade; de Oliveira Aranda, Ramon; Lima de Moraes Ramos, Sérgio Luís
Abstract: Thermobarometry and monazite U-Th-Pb geochronology of the phengite + chloritoid + biotite + garnet + kyanite bearing mica-quartz schist and of the nearby phengite + garnet bearing Córrego do Peixoto granite from Itaguara Sequence (IS) of the southern São Francisco Craton (SFC) have revealed that, at 2.05±0.05 Ga, metamorphic peak achieved ∼18.5 kbar and ∼626 °C. These pressure-temperature (P-T) conditions correspond to amphibole eclogite facies metamorphism that occurred around 60 km depth, consistent with geothermal gradient of about 10 °C/km, typical of subduction zones in continental collision settings. The continental collision-related tectonic exhumation would have triggered a decompression process of the high-pressure (HP) mica-quartz schist, which was partially melted to generate the Córrego do Peixoto granite at 2.05 Ga in P-T conditions inserted in the wet granite solidus field. The younger 1.93±0.02 Ga monazite age found in both mica-quartz schist and granite could be related to the orogenic collapse-related decompression late stage with amphibolite facies overprint. The mica-quartz schist has been modified by this late stage metamorphism, which partially overprinted primary mineral assemblages. Taking into account that ophiolites, represented in the IS by metamafic-ultramafic rocks, are typically associated to an accretionary wedge in continental collision settings, it is here suggested that mica-quartz schist is part of a probable Paleoproterozoic accretionary wedge formed above a paleo-subduction zone. It would represent a unique case of a very old accretion prism linked to a continental collision. Highlights: Rocks from Itaguara Sequence have revealed that, at 2.05 ± 0.05 Ga, metamorphic peak achieved ∼18.5 kbar and ∼626 °C. Continental collision-related tectonic exhumation triggered decompression process of the high-pressure mica-quartz schist. High-pressure mica-quartz schist was partially melted to generate the Córrego do Peixoto granite at 2.05 Ga. Mica-quartz schist is part of a probable Paleoproterozoic accretionary wedge formed above a paleo-subduction zone.